Delayed innocent bystander cell death following hypoxia in Caenorhabditis elegans - Sun, C-L (Nature Publishing Group, 2014)
After hypoxia, cells may die immediately or have a protracted course, living or dying depending on an incompletely understood set of cell autonomous and nonautonomous factors. In stroke, for example, some neurons are thought to die from direct hypoxic injury by cell autonomous primary mechanisms, whereas other so called innocent bystander neurons die from factors released from the primarily injured cells. A major limitation in identifying these factors is the inability of current in vivo models to selectively target a set of cells for hypoxic injury so that the primarily injured cells and the innocent bystanders are clearly delineated. In order to develop such a model, we generated transgenic Caenorhabditis elegans strains where 2–3% of somatic cells were made selectively sensitive to hypoxia. This was accomplished by cell type-specific wild-type rescue in either pharyngeal myocytes or GABAergic neurons of a hypoxia resistance-producing translation factor mutation. Surprisingly, hypoxic targeting of these relatively small subsets of non-essential cells produced widespread innocent bystander cell injury, behavioral dysfunction and eventual organismal death. The hypoxic injury phenotypes of the myocyte or neuron sensitized strains were virtually identical. Using this model, we show that the C. elegans insulin receptor/FOXO transcription factor pathway improves survival when activated only after hypoxic injury and blocks innocent bystander death.